Novel acousto-optic material based on Ge-Te-AgI chalcohalide glasses. Issue 9 (1st May 2021) - Ding, Shengjie; Liu, Zijun; Dai, Shixun; Liu, Chengcheng; Cao, Zhenfei
Abstract: A series of (GeTe4.3 )100−x (AgI)x (x = 5, 10, 15, 20, 25, 30 mol%) chalcohalide glasses was prepared to investigate their potential in acousto-optic (AO) materials. Detailed thermal and optical properties of these glasses have been analyzed by DSC, XRD and FTIR. Meanwhile, refractive index, density, elastic modulus, acoustic velocity and attenuation, and the AO figure of merit (M2 ) were also reported. The results indicated that all these glasses presented a single glass transition temperature (Tg ) and a single crystallization peak (Tx ), and Tg decreases while Tx increases with the addition of AgI. X-ray power diffraction investigation showed the amorphous state of these synthesized glasses. They all have a wide transparent window from 2 to 20 μm, and acoustic attenuation was observed almost linearly proportional to the frequency at room temperature. Furthermore, refractive index and density increase, while acoustic velocity and elastic modulus decreases monotonously upon introducing AgI to GeTe4.3 . The maximum refractive index (n = 3.729) and minimum acoustic velocity (V = 2.037 × 10 3 m/s) appeared in 70GeTe4.3 –30AgI glass, thereby resulting in a maximum M2 of 3671 × 10 −15 s 3 /kg at 10.6 μm. The outstandingly high M2 of this vitreous material make it attractive for far-infrared (FIR) AO modulators that require greater diffraction efficiency.